Apresentação - Horizonte, v. 13, n. 40, out./dez. 2015 - Baptista, Paulo Agostinho Nogueira (Horizonte, 2015)
Horizonte Apresentação - v. 13, n. 40, out./dez. 2015Dossiê: Desafios Teológicos do Pluralismo Religioso